2015
DOI: 10.1111/jocd.12131
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind randomized study comparing the association of Retinol and LR2412 with tretinoin 0.025% in photoaged skin

Abstract: Introduction Topical tretinoin is considered the gold standard to treat photoaged skin, but it is associated with side effects and only available upon prescription. Aim of the study To compare the efficacy, tolerance, and perception of a fixed proprietary combination (Retinol 0.2%/LR2412 2%) vs. tretinoin 0.025% cream in women with photoaged skin. Material/Methods In this randomized, parallel, double-blind, controlled clinical study, women applied to the entire face for 3 months in the morning a SPF 50 sunscre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 15 publications
(33 reference statements)
2
22
0
1
Order By: Relevance
“…Enhanced collagen synthesis is a contributing factor for improved and younger looking skin, in part, through wrinkle reduction . A recent study showed that the clinical outcome following retinol treatment did not differ from one using retinoic acid to treat photoaging . The results from our clinical study show similar effects following 12‐weeks of retinol treatment as demonstrated by significant wrinkle reduction.…”
Section: Discussionsupporting
confidence: 73%
“…Enhanced collagen synthesis is a contributing factor for improved and younger looking skin, in part, through wrinkle reduction . A recent study showed that the clinical outcome following retinol treatment did not differ from one using retinoic acid to treat photoaging . The results from our clinical study show similar effects following 12‐weeks of retinol treatment as demonstrated by significant wrinkle reduction.…”
Section: Discussionsupporting
confidence: 73%
“…Both products yielded reduced skin changes and discoloration, and resulted in a general improvement of skin condition by inhibiting photoaging. No differences were noticed between them, except that the cream with retinol was better tolerated by the skin (Bouloc & Vergnanini, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…No differences were noticed between them, except that the cream with retinol was better tolerated by the skin (Bouloc & Vergnanini, 2014). For 3 months, the study participants applied a cream consisting of a proprietary combination of 0.2% retinol with 0.025% tretinoin at night, and then SPF-50 sunscreen during the day.…”
Section: Discussionmentioning
confidence: 99%
“…Many retinoid‐based regimens have been compared alone, or in combination with other compounds . Novel retinol formulations have also been the focus of attention .…”
Section: Discussionmentioning
confidence: 99%